A Clinical Study on the Pattern of Mitral Valvular Disease in a Peripheral Tertiary Hospital in Bangladesh - Islam, AKMM; Azhar, MA; Islam, MF; Haque, MZ; Yeasmin, L (Cardiovascular Journal, 2010)
Background: Rheumatic mitral valvular disease (MVD) is a common cause of cardiovascular morbidity and mortality in Bangladesh. Many patients are diagnosed late, get maltreated, and develop complications, which can be minimized if early diagnosis could be made. Objectives: The study was carried out to determine the common symptoms and signs of mitral valvular disease in our population, to find out the incidence and pattern of complications, to list the pattern of valve lesions, to identify the common findings in different investigations and to find out the causes of delay in diagnosis. Methods: Fifty consecutive cases of isolated MVD of rheumatic origin admitted in Rajshahi Medical College Hospital, Rajshahi, Bangladesh, from July, 2002 to March, 2003 were included. Detailed history was taken, and clinical examination was performed. Chest skiagram, 12-lead ECG and echocardiography were performed in all patients. Other investigations include complete blood counts, anti-streptolysin O (ASO) titre, C-reactive protein (CRP), blood sugar, serum creatinine and routine urinalysis. Results: The peak incidence of MVD was found in the third decade (34%), 14 (28%) patients were <20 years of age. Thirty two (64%) patients had poor socio-economic condition. A previous history suggestive of rheumatic fever was found in 28 (56%). Twenty six (52%) patients received treatment from the registered medical practitioners and/or from the hospitals, 11 (22%) consulted with the quacks only, 5 (10%) had treatment from both sources. Significant delay was found in 28 (56%) patients. Illiteracy and ignorance was found to be the cause in 14 (28%) cases, poverty in 12 (24%) and misdiagnosis in 7 (14%). Six (12%) patients adopted indigenous treatment. Forty three (86%) patients experienced moderate to severe limitation of day-to-day activities all had breathlessness. Palpitation, fatigue and cough were found in 49 (98%), 45 (90%) and 42 (84%) cases respectively. Nineteen (38%) patients had haemoptysis, 15 (30%) had dysphagia. Apex beat was normally situated in 32 (64%), and shifted in 16 (32%) cases. Forty two (84%) patients had left parasternal heave and palpable P2 was found in 41 (82%) patients. Diastolic thrill was palpable in 28 (56%) cases, systolic thrill in 8 (16%) patients. The first heart sound (S1) was loud in 34 (68%) and soft in 8 (16%) cases. Mid-diastolic murmur of MS was audible in 46 (92%) cases, pansystolic murmur of mitral regurgitation in 19 (38%) patients and pansystolic murmur of tricuspid regurgitation in 10 (20%). Opening snap was found in 30 (60%), and presystolic accentuation in 27 (54%) cases. Roentgenographic study revealed moderate to huge enlargement of cardiac shadow in 29 (58%), straightening of the left border of the heart with fullness or outward bulging of the pulmonary conus in 43 (86%), double contour of the right border in 35 (70%), upper lobe diversion of pulmonary vasculature in 31 (62%), Kerley B lines in 10 (20%) and pulmonary oedema in 16 (32%) patients. The ECG showed P-mitrale in 32 (64%), atrial fibrillation in 14 (28%) and atrial flutter in 2 (4%) cases. Echocardiography revealed thickening of mitral valve leaflets in all patients, changes in subvalvular apparatus in 28 (56%) and calcification in mitral valve apparatus in 3 (6%) cases. Mitral valve area was <1 cm2 in 33 (66%), 1.0 to 1.4 cm2 in 14 (28%) and e”1.5 cm2 in 1 (2%) patients. The left atrial size was 41 to 50 mm in 20 (40%) and >50 mm in 10 (20%) cases. Two patients had left atrial thrombus. Evidence of pulmonary hypertension was found in 34 (68%) patients. Conclusion: Rheumatic MVD and the accompanying complications can be detected with an appreciable degree of accuracy by skillful clinical assessment and judicial use of simple investigations like roentgenography, electrocardiography and echocardiography which are available in many parts of our country at affordable costs. So every effort should be made to utilize these invaluable resources to tackle this public health problem more efficiently. Key Words: Rheumatic; Mitral valvular disease; Clinical. DOI: 10.3329/cardio.v3i1.6421 Cardiovasc. j. 2010; 3(1): 11-21